Updating the San: Image and Reality of an African People in the 21st Century. Robert Hitchcock, Kazunobu Ikeya, Megan Biesele and Richard Lee, editors. 2006. Senri Ethnological Studies no. 70, Osaka, Japan: National Museum of Ethnonology. ISSN 03876004; ISBN 4-901 906-43-7 C3039. v. 304 pp., maps, figures. - Muller, Carol (International Library of African Music, 2007)
pages: 118-120
Keywords: African Music